Conservative management of subcutaneous emphysema and pneumomediastinum in a COVID-19 viral pneumonia patient-case report - Ramavath, Krishna; Rao, Sidharth S.; Sindhu, Nyna; Nagaraj, Satish S.; Palle, Pranay (International Surgery Journal, 2021)
In viral pneumonia, the incidence of subcutaneous emphysema and spontaneous pneumomediastinum are rare. But it can occur due to COVID-19 SARS (severe acute respiratory syndrome) corona infection. In this condition like COVID-19 disease the underlying pathology may be due to diffuse alveolar injury. High pressure levels in the alveoli can cause to the alveoli to rupture and ultimately to forms subcutaneous emphysema. We report one case of COVID-19 admitted in the hospital and later developed subcutaneous emphysema and pneumomediastinum without mechanical ventilation. He was managed conservatively without any intervention. 45 old male without co morbidities having post COVID-19 subcutaneous emphysema and pneumomediastinum developed without mechanical ventilation and he was managed conservatively without any surgical intervention. In COVID-19 viral pneumonia patients can develop subcutaneous emphysema without mechanical ventilation and should be careful for severe pneumomediastinum which can cause death. It can be managed conservatively in hemodynamic stable condition